2015
DOI: 10.1126/science.aab0015
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor GABP selectively binds and activates the mutant TERT promoter in cancer

Abstract: Reactivation of telomerase reverse transcriptase (TERT) expression enables cells to overcome replicative senescence and escape apoptosis, fundamental steps in the initiation of human cancer. Multiple cancer types, including up to 83% of glioblastomas (GBM), harbor highly recurrent TERT promoter mutations of unknown function but specific to two nucleotide positions. We identify the functional consequence of these mutations in GBM to be recruitment of the multimeric GABP transcription factor specifically to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
518
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 478 publications
(560 citation statements)
references
References 44 publications
(38 reference statements)
22
518
1
1
Order By: Relevance
“…91 In an attempt to rationalize the molecular basis for the transcriptional effects of these somatic mutations of hTERT, it was first proposed that new ETS transcription factor binding sites are generated in the duplex form of the promoter. 45 More recently it has been proposed that GABP transcription factors can be recruited to mutant promoter elements in glioblastoma multiforme, 52 thus providing an additional mechanism for the effects of these mutations. However, these mechanisms cannot fully account for the differences in transcriptional regulation of hTERT conferred by mutant promoters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…91 In an attempt to rationalize the molecular basis for the transcriptional effects of these somatic mutations of hTERT, it was first proposed that new ETS transcription factor binding sites are generated in the duplex form of the promoter. 45 More recently it has been proposed that GABP transcription factors can be recruited to mutant promoter elements in glioblastoma multiforme, 52 thus providing an additional mechanism for the effects of these mutations. However, these mechanisms cannot fully account for the differences in transcriptional regulation of hTERT conferred by mutant promoters.…”
Section: Discussionmentioning
confidence: 99%
“…Critically, this finding also provides a direct opportunity to reverse the effects of these somatic mutations. 52 Significantly, these mutations are also localized in the 5-12 G-quadruplex with the 3:26:1 loop configuration.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Lastly, it was shown that mutations in the TERT (telomerase reverse transcriptase) promoter are linked to many types of aggressive cancer 41 , mostly by gain-of-function mutations creating ETS family 42,43 or GABP 41 transcription factor binding sites. We analyzed the TERT promoter using DeepBind ETS (ELK1/ELK4) and GABP-α models and the resulting mutation maps all show potential gain-offunction mutations corresponding to the literature.…”
Section: A N a Ly S I Smentioning
confidence: 99%
“…Recent studies identified the presence of hotspot somatic mutations in the promoter region of TERT gene, specifically the −124:C>T and −146:C>T mutations, in a range of human cancers such as bladder, gliomas, thyroid and melanoma [2][3][4][5]. These mutations have been shown to create a new binding motif sites for ETS transcription factors, which induces upregulation of TERT levels [2,5,6]. Recently, the less frequent variant C of the single nucleotide polymorphism (SNP) rs2853669 located −245 bp upstream from the ATG start site of the TERT promoter region has been shown to decrease TERT expression levels in both −124:C>T and −146:C>T mutant cases, apparently introducing a protective effect [7].…”
Section: Introductionmentioning
confidence: 99%